Current dilemma and future directions over prophylactic cranial irradiation in SCLC: a systematic review in MRI and immunotherapy era - Tang, Lingrong; Tian, Guangwei; Li, Nan (Frontiers in Oncology, 2024)
Small cell lung cancer (SCLC) is the most malignant pathological type of lung cancer with the highest mortality, and the incidence of brain metastasis (BM) is in high frequency. So far, prophylactic cranial irradiation (PCI) has been suggested as an effective treatment for preventing brain metastasis of SCLC. PCI has long been applied to limited-stage SCLC (LS-SCLC) patients who have achieved complete remission after radiotherapy and chemotherapy as a standard treatment. However, the neurocognitive decline is a major concern surrounding PCI. New therapeutic approaches targeting PCI-induced neurotoxicity, including hippocampal protection or memantine, have been increasingly incorporated into the therapeutic interventions of PCI. Helical tomotherapy, RapidArc, and Volumetric-modulated arc therapy (VMAT) with a head-tilting baseplate are recommended for hippocampal protection. Besides, in the MRI and immunotherapy era, the significance of PCI in SCLC patients is controversial. SCLC patients with PCI should be recruited in clinical trials since this is the only way to improve the existing standard of care. This review summarizes the current therapeutic strategy and dilemma over PCI for SCLC, providing a theoretical basis for clinical decision-making and suggestions for PCI practice in clinical.